Meningkatkan Inklusi Sosial dan Keberlanjutan UMK di Kabupaten Tanggamus, Provinsi Lampung melalui Pelatihan Sertifikasi Halal - Ismail, Ahyar; Andita Putri, Tursina; Pramudita, Danang (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The development of Micro and Small Enterprises (MSEs) is a key strategy for enhancing social inclusion and economic sustainability at the local level. Capacity building and the obligation for halal certification among MSEs require support from various stakeholders, including the academia. This community service activity aims to improve social inclusion and business sustainability of MSEs in Talang Padang District, Tanggamus Regency, Lampung Province, through halal certification training. Community service was conducted in three main stages: coordination and socialization, halal certification training, and monitoring and evaluation, along with participant mentoring. A total of 18 participants attended the training, with 83.33% showing an increase in knowledge about the halal concept and the process for obtaining halal certification. The evaluation results showed that 61.11% of the participants successfully obtained halal certification and incorporated the halal logo on their product packaging. The implementation of this halal certification training is expected to make a significant contribution to improving the social inclusion and business sustainability of MSEs in the region.